Sublingual house dust mite immunotherapy has no impact on decrease of circulating erythrocytes upon airway allergen challenge in allergic rhinitis - Galateja Jordakieva (Nature Portfolio, 2017)
Abstract House dust mite (HDM) allergy is a predominant cause for perennial allergic rhinitis (AR) in Europe. We recently reported that circulating erythrocyte numbers decrease after airway allergen challenge in a murine asthma model and in grass-pollen sensitized AR subjects. Consequently, we aimed to evaluate these findings in HDM sensitized AR subjects and the influence of preceding allergen immunotherapy. Seventy-seven (age 26.8 ± 7.3 years; 54.5% female) HDM-allergic rhinitis subjects previously enrolled in a randomized, monocentric sublingual immunotherapy (SLIT) trial at the Vienna Challenge Chamber (VCC) were included. Subjects had either received placebo (n = 22), low-dose HDM (n = 29) or high-dose HDM specific sublingual immunotherapy (n = 26) daily for 24 weeks. Blood sampling was performed before and after 6 hours of HDM allergen exposure. Overall, specific airway allergen challenge resulted in a significant decrease in circulating erythrocytes and hematocrit (p < 0.001), and elevation of leukocytes (p < 0.001), particularly segmented neutrophils (p < 0.001). Gender had no significant effect on the observed changes in circulating blood cells. Erythrocytes decreased and neutrophil counts increased significantly after airway allergen challenge regardless of preceding immunotherapy. These findings imply a rapid systemic mobilization of neutrophils occurring within immediate type hypersensitivity response upon a specific allergen challenge, which is possibly inversely linked with the erythrocyte numbers.